Acute Ethanol Withdrawal Impairs Contextual Learning and Enhances Cued Learning. (February 2015) - Tipps, Megan E.; Raybuck, Jonathan D.; Buck, Kari J.; Lattal, K. Matthew
<x xml:space="preserve">Abstract</x> Background Alcohol affects many of the brain regions and neural processes that support learning and memory, and these effects are thought to underlie, at least in part, the development of addiction. Although much work has been done regarding the effects of alcohol intoxication on learning and memory, little is known about the effects of acute withdrawal from a single alcohol exposure. Methods We assess the effects of acute ethanol withdrawal (6 hours postinjection with 4 g/kg ethanol) on 2 forms of fear conditioning (delay and trace fear conditioning) in C57BL/6J and DBA/2J mice. The influence of a number of experimental parameters (pre‐ and post training withdrawal exposure; foreground/background processing; training strength; and nonassociative effects) is also investigated. Results Acute ethanol withdrawal during training had a bidirectional effect on fear‐conditioned responses, decreasing contextual responses and increasing cued responses. These effects were apparent for both trace and delay conditioning in DBA/2J mice and for trace conditioning in C57BL/6J mice; however, C57BL/6J mice were selectively resistant to the effects of acute withdrawal on delay cued responses. Conclusions Our results show that acute withdrawal from a single, initial ethanol exposure is sufficient to alter long‐term learning in mice. In addition, the differences between the strains and conditioning paradigms used suggest that specific learning processes can be differentially affected by acute withdrawal in a manner that is distinct from the reported effects of both alcohol intoxication and withdrawal following chronic alcohol exposure. Thus, our results suggest a unique effect of acute alcohol withdrawal on learning and memory processes.